E-kayak: a wireless DAQ system for real time performance analysis - Bifaretti, S.; Bonaiuto, V.; Federici, L.; Gabrieli, M.; Lanotte, N. (Procedia Engineering, 2016)
The use of microelectronic measurement systems properly designed for sport performance monitoring is, in recent years, increasingly common to give helpful feedback in training of professional athletes. Different are the systems today available, some of them make use of video analysis while others are based on the measure of specific kinematic or dynamic parameters. In this paper, we present a study on a new portable data acquisition system (E-kayak - ApLab Rome Italy) for real time monitoring of the boat and paddling dynamics. The system gives real time feedback to the athlete during the training session. Moreover, the training data can then be downloaded to a PC for further analysis from the coach. The acquired data can help evaluating the paddling technique and spotting technical flaws, to improve performance. A first prototype of the system has been manufactured and at the moment is still in the testing phase. Some results of the preliminary tests are presented in this paper.